2011
DOI: 10.1111/j.1369-1600.2011.00367.x
|View full text |Cite
|
Sign up to set email alerts
|

The glycine reuptake inhibitor Org24598 and acamprosate reduce ethanol intake in the rat; tolerance development to acamprosate but not to Org24598

Abstract: Extracellular glycine modulates accumbal dopamine levels as well as ethanol-induced dopamine overflow. Glycine availability is also crucial for regulating alcohol consumption and the glycine transporter 1 (GlyT-1) inhibitor Org25935 robustly decreases alcohol intake in rats. To explore whether the alcohol-intake reducing effect of Org25935 is substance bound, we examined the effect of a different selective GlyT-1 inhibitor, Org24598, on ethanol consumption in rats and compared the effect with that of acamprosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 49 publications
(62 reference statements)
1
36
0
Order By: Relevance
“…In particular, acamprosate was found in previous studies to reduce the ADE (Spanagel et al, 1996a;Heyser et al, 1998;Lidö et al, 2012). As described in these previous studies, the calcium salt of N-acetylhomotaurinate (acamprosate) decreased the ADE in the present experiment.…”
Section: Na-aota Is Ineffective In Preclinical Animal Models But Calcsupporting
confidence: 71%
See 1 more Smart Citation
“…In particular, acamprosate was found in previous studies to reduce the ADE (Spanagel et al, 1996a;Heyser et al, 1998;Lidö et al, 2012). As described in these previous studies, the calcium salt of N-acetylhomotaurinate (acamprosate) decreased the ADE in the present experiment.…”
Section: Na-aota Is Ineffective In Preclinical Animal Models But Calcsupporting
confidence: 71%
“…In recent years, this model has become widely used for examining the efficacy of pharmacological agents in preventing compulsive alcohol consumption and relapse (Spanagel, 2009;Vengeliene et al, 2009). Moreover, acamprosate produces a reliable reduction of the ADE (Spanagel et al, 1996a;Heyser et al, 1998;Lidö et al, 2012). Critically, this effect is only observed if the calcium salt of Nacetylhomotaurinate or any other calcium salt is applied, which strongly suggests that the calcium counter ion of the acamprosate molecule is the biologically active species.…”
Section: Calcium and Acamprosate R Spanagel Et Almentioning
confidence: 95%
“…Based on previous reports (Achat-Mendes et al, 2012;Lido et al, 2012), Org 24598 (0.3, 1, and 3 mg/kg) was injected intraperitoneally with a volume of 5 ml/kg, 30 min before testing. d-amphetamine (1 mg/kg) was injected intraperitoneally with a volume of 5 ml/kg, 5 min before testing, based on evidence of improvement in probabilistic learning (Young, Khan and Powell; unpublished observations).…”
Section: Drugsmentioning
confidence: 99%
“…Especially, glycine receptors could be important regulators of ethanol induced reinforcement as antagonists targeting glycine receptors both blocks the dopamine-elevating property of ethanol in vivo, as well as prevents ethanol-induced changes in striatal neurotransmission ex vivo [79,111,112]. In addition, inhibition of the glycine transporter GlyT1 persistently reduces ethanol intake and relapse-like alcohol drinking in rats [113][114][115][116], and might thus be a pharmacological target for the treatment of alcohol abuse disorders. However, even though it was recently shown that the GlyT1 transporter inhibitor Org25935 robustly reduces the number of days with heavy drinking, the effect was not significant as compared to placebo [117].…”
Section: Astrocytic Amino Acid Transporters and Ethanolmentioning
confidence: 99%